2019
DOI: 10.1002/adts.201900081
|View full text |Cite
|
Sign up to set email alerts
|

Energy Absorption Properties of Periodic and Stochastic 3D Lattice Materials

Abstract: Architected lattices can be designed to have tailorable functionalities by controlling their constitutive elements. However, little work has been devoted to comparing energy absorption properties in different periodic three-dimensional geometries to each other and to comparable foam-like random structures. This knowledge is essential for the entire design process. In this work, the authors conduct a systematic and comprehensive computational study of the quasi-static and dynamic energy absorption properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 47 publications
2
58
0
Order By: Relevance
“…As a succession to natural instances in motion deceleration, shockwave suppression, and mechanical force reduction 14 , porous structures widely found in biological skeletal systems such as cancellous bones have been extensively investigated in numerous energy-absorbing applications [15][16][17][18] . Emulating these geometrical constructions and coupling with advanced additive manufacturing techniques in microscale, artificial cellular microarchitectures, referred to as controlled microstructural architectured (CMA) material [19][20][21] , can be structurally programmed with a controllable geometry and spatial configuration for advantageous sizedependent metamechanical properties 22,23 , such as low density but strong robustness 24 , high stiffness-to-weight ratio 25 , excellent resilience 26,27 , mechanical tunability 28,29 , and in particular, energy absorption [30][31][32][33] . Hence, by employing this cellular hierarchy for the geometric design of the tip itself, the tip-sample interaction is anticipated to be reduced.…”
mentioning
confidence: 99%
“…As a succession to natural instances in motion deceleration, shockwave suppression, and mechanical force reduction 14 , porous structures widely found in biological skeletal systems such as cancellous bones have been extensively investigated in numerous energy-absorbing applications [15][16][17][18] . Emulating these geometrical constructions and coupling with advanced additive manufacturing techniques in microscale, artificial cellular microarchitectures, referred to as controlled microstructural architectured (CMA) material [19][20][21] , can be structurally programmed with a controllable geometry and spatial configuration for advantageous sizedependent metamechanical properties 22,23 , such as low density but strong robustness 24 , high stiffness-to-weight ratio 25 , excellent resilience 26,27 , mechanical tunability 28,29 , and in particular, energy absorption [30][31][32][33] . Hence, by employing this cellular hierarchy for the geometric design of the tip itself, the tip-sample interaction is anticipated to be reduced.…”
mentioning
confidence: 99%
“…An important characteristic of cellular structures is the ability to accommodate large deformations through material and/or topological nonlinearities [ 18 , 19 ]. This property has been exploited in protective devices, such as protective military and sports equipment [ 20 ], crashworthy vehicles, shoe midsoles [ 21 ], reusable energy absorption devices, truss-like energy-absorbing medical implants [ 22 ], soft robotic actuators and structures, having negative Poisson ratio effects [ 23 , 24 ]. During an energy-absorbing large deformation process, these structures tend to decrease the maximum stress transferred through the material by evenly distributing the stress until the structure is densified [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The deformation mechanisms of architected cellular materials are rather complex to predict. Studies have shown that under a simple uniaxial compression experiment, the failure mechanism of a cellular material depends on many factors such as the cell type, parent materials, cell size, cell orientation, and post-processing history, such as heat treatment [33,53]. For example, a recent study investigating the compressive behavior of AlSi10Mg Gyroid structure revealed clear, cell size-dependent failure modes including the successive collapse of cells, brittle fractures, and the formation of shear bands.…”
Section: Introductionmentioning
confidence: 99%